Digital Communication Model in Optimizing E-Government for Improving the Quality of Public Services in Tangerang City - Raden Nita Rohmatunisa; Ade Rahmah; Fitri Susiswani Isbani (P3KM Politeknik Pertanian Negeri Samarinda, 2025)
In the digital era, governments are expected to adopt information technology to improve the efficiency, transparency, and public participation in service delivery. Tangerang City, as one of the regions implementing the Smart City concept, faces challenges in e-Government implementation, such as low digital literacy, frequent staff rotation, and limited infrastructure. Digital communication serves as a strategic bridge between the government and the public, enabling real-time interaction and public trust. This study aims to develop an adaptive and participatory digital communication model to optimize e-Government services. Employing a qualitative case study approach, data were gathered through in-depth interviews, non-participant observations, and document analysis, followed by thematic and SWOT analysis. The findings show that Tangerang City has implemented a multi-channel communication system—Instagram, TikTok, YouTube, and the “Tangerang Live” super-app—supported by six functional divisions. Key strategies include tiered content planning, mobile digital literacy programs, event-based engagement, and data-driven evaluation. This model contributes a practical framework for inclusive and sustainable digital governance.